Bodies of truth: The terrible beauty of queer performance. Issue 2 (1st October 2018) - Sampatakakis, George
This piece examines five recent performances from Greece in an attempt to map both their interventions and contributions to the development of Greek queer aesthetics. It provides a chart of this relatively unknown performative landscape and explains how the queering process works in constructing queer 'freaks', cultural mourning and a new iconography of Greekness.